Influences of educational and personal contexts on self-efficacy and job satisfaction of public elementary school teachers - Eusebio, Ellaine Joy G.; Baldera, Philip R.; C. Patiam, Aljay Marc; F. Sombria, Charton; F. Gan, Jacel Ruz; G. Castillo, Connie (International Journal of Evaluation and Research in Education (IJERE), 2025)
Enhancing teachers’ performance and sense of fulfillment in their roles is essential for advancing educational quality and promoting their overall well-being. This study investigates the determinants of teachers’ self-efficacy within a supportive school culture, as well as the factors influencing their job satisfaction, focusing on both educational and personal contexts among public elementary school teachers within a supportive school culture, focusing on educational and personal contexts. Utilizing a sample of 97 teachers from 13 schools in the Philippines, the research employs a causal-comparative design and surveys to gather data. The Kruskal-Wallis test results indicate no significant differences in self-efficacy and job satisfaction across age groups. The Mann-Whitney U test reveals a significant difference in self-efficacy between male and female teachers, with the latter reporting higher levels, while no significant gender differences were observed in job satisfaction. Likewise, no significant differences were found across career stages in both efficacy and satisfaction. A multivariate analysis of variance reveals that a supportive school culture has a significant impact on teachers’ self-efficacy and also on their job satisfaction. These results emphasize the critical role of nurturing a supportive school environment to enhance teacher well-being and effectiveness. The study provides valuable insights and practical recommendations for improving educational quality and teacher satisfaction through targeted interventions in school culture and opportunities for career advancement.